Das condições discursivas do “bolsonarismo” : crise social, econômica e política na formação de uma brasilidade conservadora no século XXI pelo Facebook - Gonçalves, Laion Loester de Paula Dias (2021)
Under corruption scandals and economic crisis during the Rousseff ("left") and Temer ("centerright") governments, Brazil experienced a process of discredit in relation to the political elite so far never seen in the current "democratic" regime. It was in this context that Jair Bolsonaro - right-wing and conservative deputy - located in the “lower clergy” of the parliament (of little national expression) emerged as the favorite in the 2018 presidential elections. Criticizing the PT governments of Lula and Dilma (who governed the country for 14 years) and with controversial speeches about blacks, women and LGBTQI+, Bolsonaro attracted the press spotlight and gained more and more supporters on the web. Given the high engagement, the following problem arose: how was it possible, in a context of formation of “bubbles” on Facebook, for Bolsonaro to gain so much support in different sectors of society? To answer this question, we sought to identify the values that were already present in Brazil and how “bolsonarism” mobilized them in favor of its discourse. The methodology used was the “snowball”, in which, starting from Jair Bolsonaro's page, other correlates were found, forming a network of 26 pages distributed on Facebook. These were classified under the field in which they were situated. Publications above 10 thousand shares were selected, favoring those with high engagement. Through the perspective of the Analysis of Argumentation in Discourse developed by Ruth Amossy, 1,439 arguments were identified with their respective discursive affiliations and doxic elements. The conclusion is that “bolsonarism” was the result of assemblage of values circulating in four distinct fields of action: political, comic, police and religious. Liberal discourses against the “politically correct” of the comic field were mobilized by “bolsonarism” to relativize Jair Bolsonaro's speeches and criticize the left as “authoritarian” and “promoters of censorship”. Arguments against human rights in the police field were managed by “bolsonarism” under fascist discourses. In the religious field, the Christian discourse of “child innocence” was mobilized by “Bolsonarism” to criticize gender and sexuality policies in schools. Likewise, the biblical story of David (“Bolsonaro”) against Goliath (“PT”) inserted the candidate into the (neo)Pentecostal worldview of the battle between “God” and the “Devil”. In the political field and under republican speeches, Bolsonaro led the fight against corruption. This speech reached the police and religious field. All of these values came together through patriotic discourses of “individual sacrifice” for the benefit of the “fatherland” and produced a high level of collective engagement. Being proudly “Brazilian” has become synonymous with being “Christian”, “worker”, “honest” and “civilized”. This may indicate a socio-discursive conformation capable of producing a properly conservative “national identity” in Brazilian satiety.